Single-molecule electronic materials. Conductance of π-conjugated oligomers within quasi-correlated tight-binding model - Luzanov, A.V. (Functional Materials, 2019)
For computing electric conductance through organic nanowire of conjugated type we make use of the recently proposed quasi-correlated tight-binding (QCTB) method. The appropriate Green's function (GF) matrices are constructed, and simple numerical algorithms are given for them. Moreover, the GF analytical solutions are obtained for finite-sized polyene chains and other systems. A special attention is paid to conjugated oligomers with various strength of electron correlation. In particular, we find that in polyquinoids the conventional Huckel and restricted Hartree-Fock methods lead, in contrast to QCTB, to a nonphysical increase of GF matrix elements for far separate contacts.